Silencing of Sly-miR171d increased the expression of GRAS24 and enhanced postharvest chilling tolerance of tomato fruit - Xing, Zengting; Huang, Taishan; Zhao, Keyan; Meng, Lanhuan; Song, Hongmiao; Zhang, Zhengke; Xu, Xiangbin; Liu, Songbai (Frontiers in Plant Science, 2022)
The role of Sly-miR171d on tomato fruit chilling injury (CI) was investigated. The results showed that silencing the endogenous Sly-miR171d effectively delayed the increase of CI and electrolyte leakage (EL) in tomato fruit, and maintained fruit firmness and quality. After low temperature storage, the expression of target gene GRAS24 increased in STTM-miR171d tomato fruit, the level of GA3 anabolism and the expression of CBF1, an important regulator of cold resistance, both increased in STTM-miR171d tomato fruit, indicated that silencing the Sly-miR171d can improve the resistance ability of postharvest tomato fruit to chilling tolerance.